Taxonomic study of the genus Dactylolabis Osten Sacken, 1860 of Japan (Diptera: Limoniidae) - Kato, Daichi (Zootaxa, 2023)
Japanese species of the genus Dactylolabis Osten Sacken, 1860 are revised. One new species, D. kyororo sp. nov. is described and the two other species of the genus, D. diluta Alexander, 1922 and D. longicauda Alexander, 1922, are redescribed, with images of the habitus and wings, and drawings of the terminalia. A subspecies of D. longicauda Alexander, 1922 described from Yakushima Island, D. longicauda megastylata Alexander, 1930, is synonymized with the nominotypical subspecies. A key to the species is provided.